2001
DOI: 10.1076/orbi.20.3.189.2628
|View full text |Cite
|
Sign up to set email alerts
|

Mini Monoka silicone monocanalicular lacrimal stents: Subjective and objective outcomes

Abstract: BACKGROUND. Canalicular injuries and anomalies are relatively common. Despite this, controversy still exists regarding the indications for surgery and best surgical methods. The most favourable intervention would be one that is simple, associated with a high level of subjective and objective outcome, and does not threaten the uninjured or unaffected part of the lacrimal drainage system. This study assesses outcomes of intervention with the Mini Monoka silicone monocanalicular lacrimal stent. METHOD. A single c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 12 publications
1
18
2
4
Order By: Relevance
“…3,22 The Mini-Monoka (FCI Ophthalmics, Marshfield Hills, MA) and Monostent (Eagle Vision Inc., Memphis, TN) stents were developed to prevent the various complications of silicone monocanalicular stents. Anastas et al 8 ) from the inferior punctum, its distal portion was unexpectedly found to be distorted. Note that the Monostent (Eagle Vision Inc.) has a larger inner diameter, which allows a 23-gauge needle to be passed through the plug.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…3,22 The Mini-Monoka (FCI Ophthalmics, Marshfield Hills, MA) and Monostent (Eagle Vision Inc., Memphis, TN) stents were developed to prevent the various complications of silicone monocanalicular stents. Anastas et al 8 ) from the inferior punctum, its distal portion was unexpectedly found to be distorted. Note that the Monostent (Eagle Vision Inc.) has a larger inner diameter, which allows a 23-gauge needle to be passed through the plug.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, silicone tubing has achieved great popularity due to its softness, flexibility, and tolerance by pericanalicular tissues. 8 Although some studies have recommended limiting silicone stent placement for 3 to 9 months, because it might act as a nidus for granuloma formation and infection, 32,33 we leave stents in situ for as long as possible, even permanently, if the patient has no complaint of epiphora.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Success rate of monocanalicular intubation method has been reported in the range of 60% to 100%. [21][22][23]30,32,33] High rate of success has also been described in some studies conducted in our country. Argın et al, [12] Yaman et al, [29] and Oltulu et al reported success rate of 100%.…”
Section: Discussionmentioning
confidence: 95%
“…[21] However, in 19-patient series of Leibovitch et al, early tube dislocation was not observed in any patient. [22] Risk of early tube dislocation can increase, especially in children, due to rubbing and scratching.…”
Section: Discussionmentioning
confidence: 96%
“…Premature stent extrusion and stent migration are the major disadvantages of this technique and can result in a poor surgical outcome. Anastas et al reported premature extrusion in 29% and stent migration in 14% of 13 cases [12]. Over-dilation of the punctum is a risk factor for stent migration [13].…”
Section: Discussionmentioning
confidence: 99%